Resource utilization capability of bacteria predicts their invasion potential in soil. (February 2015) - Ma, Chao; Liu, Manqiang; Wang, Hui; Chen, Chenying; Fan, Wenqing; Griffiths, Bryan; Li, Huixin
Abstract: Biological invasion is governed by intrinsic and extrinsic factors, but few studies have explored the interactive roles of species traits and disturbance in soil microbial invasion. A microcosm experiment was conducted to compare the survival of four non-indigenous bacteria in soil previously subjected to heating disturbance (60 °C, 24 h). The survival of non-indigenous bacteria was positively correlated with their utilization capability of saccharose and glucose 3 days after inoculation, and positively with maltose, saccharose, D-mannitol, glycerol, glucose and amylose 42 days following inoculation. Disturbance increased resource availability and also reduced diversity of the native microbial community. Bacteria survival was significantly increased in disturbed soil, especially for the bacteria with weak resource utilization capability. Bacterial invasion potential was determined by resource utilization capability, with that dependence increased with incubation duration and reduced if soil was initially disturbed. Highlights: Soil bacterial microcosm is a good system for studying invasion ecology. Survival of four non-indigenous bacteria was compared following disturbance. Resource utilization capability determines bacterial survival potential. Promoting effects of disturbance on bacteria survival vary with bacterial strains.